Vier Bücher der Ritterschafft - Vegetius Renatus, Flavius (Heinrich Stayner, 1529)
First edition published by Heinrich Stayner of De re militari, a classic work on the science of making war by Publius Flavius Vegetius Renatus, commonly referred to as Vegetius, a writer from the Later Roman Empire (circa 4th century). The first German text edition appeared circa 1476; the second (Erfurt, 1511) and this 1529 edition were published with a new translation and woodcuts, which variously depict underwater diving suits, siege equipment, cannons, and air mattresses for the comfort of soldiers in the field. Notably, Vegetius Renatus' classic text is brought up to the early Renaissance with depictions of more contemporary technologies, including handguns, cannons, and fireworks. All 121 full-page woodcuts and 2 half-page woodcuts from the volume are digitized here, with additional item-level description available for select woodcuts.
Keywords: Military art and science